Facial Nerve Schwannoma Treatment with Stereotactic Radiosurgery (SRS) versus Resection followed by SRS: Outcomes and a Management Protocol - Dayawansa, Sam; Dumot, Chloe; Mantziaris, Georgios; Mehta, Gautam U.; Lekovic, Gregory P.; Kondziolka, Douglas; Mathieu, David; Reda, Wael A.; Liscak, Roman; Cheng-chia, Lee; Kaufmann, Anthony M.; Barnet, Gene; Trifiletti, Daniel M.; Lunsford, L Dade; Sheehan, Jason (Journal of Neurological Surgery Part B: Skull Base, 2022)
Background Stereotactic radiosurgery (SRS) and resection are treatment options for patients with facial nerve schwannomas without mass effect.Objective This article evaluates outcomes of patients treated with SRS versus resection + SRS.Method We retrospectively compared 43 patients treated with SRS to 12 patients treated with resection + SRS. The primary study outcome was unfavorable combined endpoint, defined as worsening or new clinical symptoms, and/or tumor radiological progression. SRS (38.81 ± 5.3) and resection + SRS (67.14 ± 11.8) groups had similar clinical follow-ups.Results At the time of SRS, the tumor volumes of SRS (mean ± standard error; 1.83 ± 0.35 mL) and resection + SRS (2.51 ± 0.75 mL) groups were similar. SRS (12.15 ± 0.08 Gy) and resection + SRS (12.16 ± 0.14 Gy) groups received similar radiation doses. SRS group (42/43, 98%) had better local tumor control than the resection + SRS group (10/12, 83%, p = 0.04). Most of SRS (32/43, 74%) and resection + SRS (10/12, 83%) group patients reached a favorable combined endpoint following SRS (p = 0.52). Considering surgical associated side effects, only 2/10 patients of the resection + SRS group reached a favorable endpoint (p < 0.001).Patients of SRS group, who are > 34 years old (p = 0.02), have larger tumors (> 4 mL, 0.04), internal auditory canal (IAC) segment tumor involvement (p = 0.01) were more likely to reach an unfavorable endpoint. Resection + SRS group patients did not show such a difference.Conclusion While resection is still needed for larger tumors, SRS offers better clinical and radiological outcomes compared to resection followed by SRS for facial schwannomas. Younger age, smaller tumors, and non-IAC situated tumors are factors that portend a favorable outcome.
Keywords: facial nerve; schwannoma; stereotactic radiosurgery; internal auditory canal